Hospital Liability for Negligence of Medical Personnel Found in Hospitals Following the Issuance of the Constitutional Court Decision Number 82/PUU-XIII/2015 - Khoironi, Moh. Lu'ay; Nazidah, Febrianti Putri Ainun (Arena Hukum, 2024)
As an important element in welfare efforts, everyone has the right to health services, like those provided by hospitals seeking to treat visiting patients. This measure certainly entails several elements, including health workers and medical personnel as in line with the Constitutional Court Decision Number 82 / PUU-XII / 2015, declaring Article 11, Paragraph (1) letter a of Law Number 44 of 2009 concerning Hospitals no longer valid, thus removing the existence of doctors and dentists as health workers. Under this decision, Doctors and dentists are identified as medical personnel. Article 46 of Law Number 44 of 2009 concerning Hospitals regulates that in the event of a malpractice that causes harm by health workers, a hospital is responsible for this misconduct unless the practice is performed outside of the hospital. However, doctors and dentists are no longer identified as health workers under the decision. In other words, any negligence committed by doctors and dentists should no longer hold the hospital liable This research employs a normative method supported by statutory and case approaches, while the legal materials were analysed based on descriptive-analytical methods